Modeling of grid-connected inverter using grid-forming technology - Nguyễn Quang Minh; Cao Thành Trung; Hoàng Anh (Journal of Military Science and Technology, 2024)
Currently, grid-forming inverter technology is attracting attention and research investment worldwide, as it represents a critical step toward achieving a society powered entirely by renewable energy. However, foundational knowledge on this technology remains limited. This paper presents the control system structure for a grid-forming inverter with a simple design approach. First, a general state-space model of the system is developed to assess stability. Then, the system’s operational parameters are verified, and simulations are conducted on PSCAD software for further analysis. The results clarify the key concepts and structure of grid-forming technology, propose a method for stability assessment, and provide guidance on utilizing simulation tools for this system.